2019
DOI: 10.2147/cmar.s171517
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rhein shows potent efficacy against non-small-cell lung cancer through inhibiting the STAT3 pathway</p>

Abstract: Background: Non-small-cell lung cancer (NSCLC) comprises about 85% of all lung cancers and is usually diagnosed at an advanced stage with poor prognosis. The IL-6/STAT3 signaling pathway plays a pivotal role in NSCLC biology. Rhein is a lipophilic anthraquinone extensively found in medicinal herbs. Emerging evidence suggests that Rhein has significant antitumor effects, supporting the potential uses of Rhein as an antitumor agent. Methods: Cell viability and colony formation were performed to examine Rhein's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…In vitro Caco-2 p-ERK1/2↑ (at higher concentrations of rhein) [150] In vitro HT29, HCT116, Colo205, SW620 HIF-1α↓, PD-L1↓, VEGF↓, COX-2↓, galectin-1↓ [98] In vitro HCT116, SW620 p-STAT3↓ [151] Glioma In vitro F98 ERK1/2↓ [152] In vitro T98G, U87, U251 Ac-K100↑, NDRG1↑ [153] Leukemia In vivo EU-1 injected SCID mice MDM2↓, p53↑ [154] In vitro HL-60 Cleaved caspase↑, cleaved PARP↑, cleaved Bid↑, ∆Ψm↓ [145] In vitro NB4 p-ERK↑, Caspase-3↑ [155] Liver cancer In vitro and in vivo HepG2, HepG2 injected BALB/c-nu mice β-catenin↓, S phase arrest↑ [111] In vitro HepG2 CD95↑, p53↑, p21/WAF↑, mCD95L↑, sCD95L↑ [96] In vitro BEL-7402 c-Myc↓, Caspase-3↑, S phase arrest↑ [54] In vitro SMMC-7721, SMMC-7721/DOX ATP synthesis↓, inner ∆Ψm↓ [156] In vitro HepG2, Huh7 ROS↑, p-c-Jun↑, Caspase-3↑ [55] Lung cancer In vitro and in vivo PC-9, H460, A549, H460 xenograft mice STAT3↓, Bax↑, Bcl-2↓, G2/M phase arrest↑ [157] In vitro A549 p-PI3K↓, Akt↓, mTOR↓, Bcl-2↓ [158] In vitro A549 G0/G1 phase arrest↑, GADD153↑, GRP78↑, Cyt c↑,…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro Caco-2 p-ERK1/2↑ (at higher concentrations of rhein) [150] In vitro HT29, HCT116, Colo205, SW620 HIF-1α↓, PD-L1↓, VEGF↓, COX-2↓, galectin-1↓ [98] In vitro HCT116, SW620 p-STAT3↓ [151] Glioma In vitro F98 ERK1/2↓ [152] In vitro T98G, U87, U251 Ac-K100↑, NDRG1↑ [153] Leukemia In vivo EU-1 injected SCID mice MDM2↓, p53↑ [154] In vitro HL-60 Cleaved caspase↑, cleaved PARP↑, cleaved Bid↑, ∆Ψm↓ [145] In vitro NB4 p-ERK↑, Caspase-3↑ [155] Liver cancer In vitro and in vivo HepG2, HepG2 injected BALB/c-nu mice β-catenin↓, S phase arrest↑ [111] In vitro HepG2 CD95↑, p53↑, p21/WAF↑, mCD95L↑, sCD95L↑ [96] In vitro BEL-7402 c-Myc↓, Caspase-3↑, S phase arrest↑ [54] In vitro SMMC-7721, SMMC-7721/DOX ATP synthesis↓, inner ∆Ψm↓ [156] In vitro HepG2, Huh7 ROS↑, p-c-Jun↑, Caspase-3↑ [55] Lung cancer In vitro and in vivo PC-9, H460, A549, H460 xenograft mice STAT3↓, Bax↑, Bcl-2↓, G2/M phase arrest↑ [157] In vitro A549 p-PI3K↓, Akt↓, mTOR↓, Bcl-2↓ [158] In vitro A549 G0/G1 phase arrest↑, GADD153↑, GRP78↑, Cyt c↑,…”
Section: Colon Cancermentioning
confidence: 99%
“…Some preclinical studies also showed the regulation of STAT3, Bax, and Bcl-2 expression pathway by rhein in A549 cells. It was shown that the treatment of rhein halted the cell cycle at G2/M phase via downregulation of cyclin B1, MDM2, and p-53 expression levels in H460 and PC-9 cells [157].…”
Section: Lung Cancermentioning
confidence: 99%
“…Rhein is a natural anthraquinone found in several medicinal plants [10], and it has been reported to possess a wide range of biological activities. Recent studies have demonstrated that rhein exhibited potent e cacy in inhibiting tumor growth [11,12,17,30]. However, the mechanisms underlying its anticancer effects of rhein remain poorly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Rhein (4, 5-dihydroxyanthraquinone-2carboxylic acid) is a natural anthraquinone found in several medicinal plants, including Rheum palmatum, Polygonum multi orum, Aloe barbadensis, and Cassia tora [10]. A previous study suggested that rhein strongly inhibited non-small-cell lung cancer cells growth in vitro and in vivo by suppressing STAT3 pathway [11]. Rhein also induced HepaRG cell death via S phase cell cycle arrest and increased apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…The STAT3 signal transduction pathway plays a key role in the biology of NSCLC. Yang et al [23] found that rhein, a lipophilic anthraquinone, might exert its antilung cancer effect by inhibition of STAT3. Rhein can markedly reduce viabilities and induce apoptosis in human lung cancer A549, PC9, and H460 cells.…”
Section: Quinonoids Inhibit Proliferation and Induce Apoptosismentioning
confidence: 99%